2021
DOI: 10.3390/life11080742
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein Relationship with Metabolic Disorders and Cardiovascular Diseases Risk Factors

Abstract: Background. Chronic inflammation is considered to be involved in the development of CVD. It is important to find a simple test that enables the identification of patients at risk and that may be used in primary care. The aim of this study is to investigate the associations of high-sensitivity C-reactive protein (hsCRP) with selected factors—age, gender, obesity, dyslipidemia, diabetes, hyperuricemia, vitamin D-25(OH)D, cardiovascular diseases (CVD), coronary heart disease, cerebrovascular disease, and hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Many studies from different populations have noted a statistically significant relationship between the concentration of CRP and the occurrence of dyslipidemia in T2DM [ 48 , 49 ]. However, according to a previous study, higher CRP levels were not associated with elevated concentrations of lipid parameters [ 50 ].…”
Section: Discussionmentioning
confidence: 90%
“…Many studies from different populations have noted a statistically significant relationship between the concentration of CRP and the occurrence of dyslipidemia in T2DM [ 48 , 49 ]. However, according to a previous study, higher CRP levels were not associated with elevated concentrations of lipid parameters [ 50 ].…”
Section: Discussionmentioning
confidence: 90%
“…A recent cross-sectional analysis of older females with periodontal diseases and a randomized trial of female adults with depressive symptoms both found no associations between vitamin D biomarkers and CRP concentrations [ 21 , 29 ]. In contrast, 2 studies of patients with cardiovascular diseases found an inverse association between vitamin D and high-sensitive CRP biomarkers [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of pregnant females in China indicated a modifying relationship between lipid profile, vitamin D, and CRP suggesting that high 25(OH)D concentrations prevent the rise of high-sensitive CRP induced by high concentrations of lipid biomarkers [ 34 ]. A study of US adult patients with cardiovascular diseases also found positive association between BMI and high-sensitive CRP [ 30 ], and another study of Tanzanian adult patients with tuberculosis reported a positive association between BMI and vitamin D [ 35 ]. Several mechanisms can account for the relationship between body fat, vitamin D, and inflammation such as increased uptake of vitamin D by adipose tissue, reduced sun exposure that is indispensable for cutaneous vitamin D synthesis, and negative feedback loop on hepatic synthesis of vitamin D [ 36 ]; however, more studies with more sensitive measurements of body fat are needed to investigate the complex relationship between body fat, vitamin D, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in methodologies have enabled the detection of hsCRP, associated with chronic non‐communicable diseases (NCDs) characterized by an activated proinflammatory state 1 . Numerous investigations have substantiated the notion that hsCRP, even when falling within the established clinical normal range, holds significance as an antecedent for the onset of hypertension, 2 type 2 diabetes, 3–5 and metabolic syndrome (MetS) 6,7 . Furthermore, it might be an autonomous prognostic factor indicative of the initial phases of cardiovascular disease (CVD) 8–11 .…”
Section: Introductionmentioning
confidence: 99%